2011
DOI: 10.2106/jbjs.i.01673
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of the Coronoid Process in Elbow Fracture-Dislocations

Abstract: For terrible triad injuries, greater stability with fewer complications was achieved with use of the suture lasso technique for coronoid fracture fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(130 citation statements)
references
References 17 publications
3
118
2
4
Order By: Relevance
“…At 2 years, the median QuickDASH score of 7 is consistently lower than QuickDASH scores reported in previous articles on similar types of injuries treated with a hinged fixator (P 25 -P 75 , 15-28 points) [8,13,32,34] or treated with ligament repair (P 25 -P 75 , 15-28 points) [6,8,10,42]. The slight disability is paralleled by high scores on the additional patient-reported functional outcome measures.…”
Section: Discussionmentioning
confidence: 60%
“…At 2 years, the median QuickDASH score of 7 is consistently lower than QuickDASH scores reported in previous articles on similar types of injuries treated with a hinged fixator (P 25 -P 75 , 15-28 points) [8,13,32,34] or treated with ligament repair (P 25 -P 75 , 15-28 points) [6,8,10,42]. The slight disability is paralleled by high scores on the additional patient-reported functional outcome measures.…”
Section: Discussionmentioning
confidence: 60%
“…First, removal of the radial head for planned arthroplasty allows for better visualization of the coronoid fracture fragment. The importance of adequate coronoid fixation in terrible triad injuries has been documented previously [5,7,8,11,21]. Improved visualization through the existing lateral incision may potentially allow for better reduction and fixation, regardless of fixation technique.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously published a report on this series of patients, specifically evaluating surgical outcomes based on the fixation method of the coronoid fracture fragment [7]. That analysis revealed that a suture lasso technique was superior to suture anchors or lag screws before and after LUCL repair.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations